Fluidic Infiltrative Assembly of 3D Hydrogel with Heterogeneous Composition and Function. (16th June 2021) - Escobar, Alberto Ranier; Zanganeh, Somayeh; Sullivan, Jonathan; Li, Lei; Dautta, Manik; Lee, Jaeho; Tseng, Peter
Abstract: 3D hydrogels are powerful, multifunctional materials that are poised to become a building block in next‐generation systems. Modern schemes to print complex 3D hydrogels are advancing rapidly; however, they possess several limitations including—but not limited to—polymer incompatibility or difficulty in imparting continuous heterogeneity in composition or function. Here, a simple strategy of synthesizing programmable hydrogel systems with tunable form and function in 3D is presented. This approach utilizes commercially available stereolithographic printer/resin to fabricate high‐resolution molds followed by the programmed infiltration and gelation of hydrogel prepolymer. This mold is then sacrificed to yield 3D, multifunctional hydrogels exhibiting user‐defined heterogeneity. The approach is compatible with numerous in‐situ gelling polymers and modifiers ranging from interpenetrating networks of organic or synthetic polymers to functional materials possessing dense concentrations of nanomaterials or fluorescent markers. Accessible and versatile, this approach allows the fabrication of complex, multimaterial constructs with tunable 3D environmental responses inaccessible to well‐established hydrogel 3D printing methods. Abstract : Fluidic infiltrative assembly is studied as a method of synthesizing 3D hydrogel monoliths that exhibit programmable, heterogeneous composition, and function. This approach circumvents constraints associated with direct hydrogel 3D printing strategies and enables the fabrication of gradient hydrogel‐systems that leverage a wide array of material and modifier choices with intelligent structural design.